Nano-Porous Light-Emitting Silicon Chip as a Potential Biosensor Platform - Zhang, Juankun; Zhang, Weiliang; Dong, Shanmu; Turner, Anthony P. F.; Fan, Qingjie; Jia, Shiru (Taylor and Francis, 2008)
Nano-porous silicon (PS) offers a potential platform for biosensors with benefits both in terms of light emission and the large functional surface area. A light emitting PS chip with a stable and functional surface was fabricated in our laboratory. When protein was deposited on it, the light emission was reduced in proportion to the protein concentration. Based on this property, we developed a rudimentary demonstration of a label-free sensor to detect bovine serum albumin (BSA). A serial concentration of BSA was applied to the light chip and the reduction in light emission was measured. The reduction of the light intensity was linearly related to the concentration of the BSA at concentrations below 10-5 M. The detection limit was 8×10-9 M.
Keywords: Nano-porous silicon; Label-free biosensor; Optical sensor